High-Temperature Corrosion Behavior of Incoloy 800H Alloy in the Impure Helium Environment - Wei Zheng; Huang Zhang; Bin Du; Haoxiang Li; Huaqiang Yin; Xuedong He; Tao Ma (Science and Technology of Nuclear Installations)
The helium coolant in the primary circuit of the high-temperature gas-cooled reactor (HTGR) contains traces of impurities, which can induce the corrosion of superalloys when exposed to elevated temperatures. The superalloy damage caused by the corrosion could threaten the safe operation of the reactor. In this work, the corrosion behavior of a representative superalloy (chromium-rich iron base alloy Incoloy 800H) was investigated under the impure helium at different typical temperatures of HTGR. An experimental setup developed for studying the high-temperature corrosion of superalloys was used to investigate the chemical reactions and corrosion behaviors of Incoloy 800H. It was found that CO2 is an important oxygen source in the reaction with chromium, and CO is released as the product. In addition, the observation and computation of the critical temperature (TC) of the reaction between CO2 and carbon in the alloy show that TC is much lower than that (TA) of the microclimate reaction, which indicates that CO2 can protect the scale from destruction. Furthermore, the slight decarbonization of the alloy was found above TC. Also, a model developed by the thermodynamic analysis was proposed to explain the mechanism of slight decarbonization and predict the critical temperature when the CO2-C reaction occurs. This work presents a guideline for protecting the oxide scale of superalloys used in HTGR.